Kontrol Geologi Terhadap Alterasi dan Mineralisasi Daerah Jladri, Karangbolong, Jawa Tengah - Aloysius Surya Putra Dara Lay; Qodri, Muhammad Fatih (ReTII, 2023)
Hydrothermal alteration is the process of changing primary minerals in rocks due to interactions with hydrothermal fluids. The Karangbolong area is an ancient volcanic mountain zone that allows for the formation of hydrothermal alteration processes and the potential for the formation of interesting economic minerals to study. This study aims to determine the geological conditions that support the process of hydrothermal alteration and mineralization potential in the Karangbolong area. Hydrothermal alteration minerals will form certain alteration zones and can indicate the conditions of their formation environment. Mapping the hydothermal alteration zone aims to determine the potential for mineralization and the types of deposits formed. The method used is mapping with a scale of 1:5000 with a petrological and petrographic approach. The phyllic, argillic and propylitic zones were found in the study area and indicate potential mineralization in the Karangbolong area